2012
DOI: 10.1292/jvms.11-0554
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Lymphocyte Subsets as a Prognostic Indicator of Mortality and Morbidity in Healthy Dogs

Abstract: ABSTRACT. To evaluate the relationship among immune status and increased morbidity and mortality, peripheral blood lymphocytes (CD3 + , CD4 + , CD8 + and CD21 + cells) from 32 healthy dogs over 8 years of age were analyzed. Twenty-five of the 32 dogs were followed-up for 3 years after the analysis; and 14 dogs were found to be diseased, and nine dogs died. There was no notable difference between the ages of the dogs that died compared with the ones that survived. The relative percentage of CD4 + and the CD4 + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…It has recently been shown that the ratio of CD4 + /CD8 + provides information about the immune status and further predicts the risk of aging-related diseases and mortality [ 41 ]. In the bovine it was shown that a ratio higher than 2 indicates a proper immune status [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that the ratio of CD4 + /CD8 + provides information about the immune status and further predicts the risk of aging-related diseases and mortality [ 41 ]. In the bovine it was shown that a ratio higher than 2 indicates a proper immune status [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many similarities between the dog and other animals have been demonstrated, establishing canine antibody equivalents of CD3, CD5, CD4, CD8 used to label lymphocyte T-cell subsets from peripheral blood (McSweeney et al 1998;Hardy et al 2013). Furthermore, in healthy beagle dogs over 8 years old, where tumour incidence becomes higher, the immune status of CD3, CD4, CD8 and CD21 could predict future morbidity and mortality (Watabe et al 2012). By turn, the discovery of CD34 as an immature haematopoietic cell surface antigen and the production of anti CD34-monoclonal antibodies provided an important tool to study haematologic malignancies (Cobbold et al 1994;McSweeney et al 1998;Ostronoff et al 2008;Williams 2008).…”
Section: Flow Cytometry Peripheral Blood Leukocyte Subsets Long-tementioning
confidence: 99%
“…A minimum of 200 white blood cells was counted by two different pathologists. In flow cytometry we established the number of cells for each subpopulation; using an absolute cell counting (cell number/μl of whole blood), and with the percentage gated, which is the frequency (%) of events in the subpopulation compared with all the acquired events (Watabe et al 2012). …”
Section: Cytological Evaluationmentioning
confidence: 99%
“…Decreased lymphocyte subsets due to aging or speci c diseases (4-7) and immunode ciency due to congenital B-cell depletion (8,9) have been reported. Another study proposed that decreased lymphocyte subsets may be useful as a prognostic indicator of mortality (10). However, lymphocyte subset analysis is not often used clinically in small animal practice.…”
mentioning
confidence: 99%